A summary of high quality online information resources for parents with cancer who have adolescent and young adult children: A scoping review. Issue 12 (11th November 2019) - Weeks, Nicole; McDonald, Fiona E.J.; Patterson, Pandora; Konings, Stephanie; Coad, Jane
Abstract: Objective: Parents with cancer want information about maintaining family functioning despite cancer. This scoping review assesses what online information resources are available to help parents with cancer maintain family functioning, the quality of the available information, and whether resources provide specific advice for parents of adolescent and young adult (AYA) children. Methods: To identify available relevant English‐language online information resources, we imitated a parental online information search using three search engines (Google, Yahoo, and Bing). Online resources from the last 10 years for parents with cancer addressing family functioning were included. These resources were rated using the DISCERN instrument—a tool for rating the reliability and quality of health information resources. Results: 684 results were screened and 33 online information resources from the USA, UK, Australia, Canada, and Ireland met the inclusion criteria. Average DISCERN quality was 54/80 (95% CI:50‐58), which is typical for online health information. The highest rated resources provided information for parents on supporting their AYA children's needs for information and support with feelings, but few comprehensively covered other specific AYA needs. Details on resource weaknesses as identified by the DISCERN are presented. Conclusions: Several high‐quality resources for parents with cancer were identified from multiple countries, allowing health professionals internationally to direct patients with cancer to relevant high quality online information. Highlighted limitations in resource quality and scope will guide future resource development and revision, ensuring more comprehensive high quality information is available to support families affected by parental cancer internationally.